Modal equity of accessibility to healthcare in Recife, Brazil - Boer Cui; Genevieve Boisjoly; Bernardo Serra; Ahmed El-Geneidy (Journal of Transport and Land Use)
In the context of increasing urbanization and income inequality, transport professionals in the Global South need to be prepared to effectively plan for the needs of various groups within the population, particularly for those regarding health and well-being. Accessibility is widely used as a performance measure for land use and transport systems; it measures people’s ease of reaching desired destinations and incorporates mode, time, and/or cost constraints. Considerable differences exist in the level of accessibility experienced by different mode users in reaching healthcare facilities, which calls for additional equity considerations given the prevailing socio-demographic characteristics of the users of various modes and the importance of healthcare facilities as a destination. In this study, we explore the distribution of accessibility to healthcare facilities by public transport and by car in Recife, Brazil, through an equity assessment to identify areas with low accessibility using these modes at different times of day. In general, the higher accessibility of public transport as well as greater modal equity was observed in central regions of Recife, whereas the periphery, where many low-income census tracts can be found, experiences significant inequity when it comes to access by both modes to healthcare facilities. This analysis allowed us to classify locations to access impoverished, access absolutely impoverished, and access impoverished by public transport areas, which can be targeted with appropriate land use and public transport policy interventions. This paper can be of value to professionals and researchers working toward equitable land use and transport systems in the Global South.